DAMPAK KEBIJAKAN ANTI TEMBAKAU TERHADAP STRATEGI NAFKAH PETANI TEMBAKAU MADURA (Studi Kasus Desa Panaguan Kecamatan Proppo Pamekasan) - Musfiqur Rahman; Slamet Widodo (MediaTrend, 2015)
The objectives of this study is to identify and to know policies released by government which is related with demarcation of cigarette circulation and explaining maintenance strategy of tobacco’s farmer in Panaguan village, Proppo district. Research method of this study is descriptive qualitative method. Observation, interview, library research, and documentation are used as technique of collecting data. The result of this study indicates that government has released some policies of cigarette circulation demarcation. However, those policies have given negative impact for cigarette industry and its perpetrator. They have caused scale degradation of tobacco absorption from warehouse. That condition begets tobacco’s price not stable. Moreover, development of Indonesia’s cigarette industry descends progressively every year. Maintenance strategy applied by Panaguan village’s inhabitant is intensification and efficiency strategy, tumpang sari strategy, double maintenance patterns, commodity manipulation strategy, migration, and also exploit local institute